Competency- Based Human Resource Development in Nepalese Commercial Banks - Niraula, Ganesh Prasad; Kharel, Shreekrishna (Patan Prospective Journal, 2023)
The objective of this study is to find the competency based human resource development in Nepalese commercial banks. Simple random sampling was used in this study to gather data, and descriptive and causal comparative research approaches were used to get results. While inferential statistics were used for result analysis, descriptive statistics were used to explain respondents' perspectives on competency variables. 396 respondents were given a typical structured questionnaire to complete. Utilizing SPSS version 26, data analysis was carried out. Staffing and selection, education and training, organizational growth, and performance management were the four independent variables included in the study. Development of human resources was the dependent variable. The result of this research shows that there is positive relationship between competency and human resource development. It can be mentioned that the independent variables have positively impacted human resource development. The coefficient of determination test resulted in an Adjusted R Square of 54.10 percent which indicates a good correlation between the independent and dependent variable. The remaining percent 45.90 are influenced by other variables aside from this .The higher management and the departmental managers are recommended to focus on the enhancement of competency on the employees of commercial banks in Nepal.